Preparation of chitin-amphipathic anion/quaternary ammonium salt ecofriendly dressing and its effect on wound healing in mice - Zhou D (Dove Medical Press, 2018)
Daijun Zhou,1–3 Ruijia Yang,4 Tao Yang,1–3 Malcolm Xing,1–4 Gaoxing Luo1–3 1Institute of Burn Research, 2State Key Laboratory of Trauma, Burn and Combined Injury, 3Key Laboratory of Proteomics of Chongqing, Southwest Hospital, Army Medical University (Third Military Medical University), Chongqing, China; 4Department of Mechanical Engineering, University of Manitoba, Winnipeg, MB, Canada Objective: This study aimed to prepare an eco-friendly dressing using a chitin-derived membrane with amphipathic anion/quaternary ammonium salt designed for antibacterial purposes.Methods: Four dressings were prepared and group A was chitin, group B was chitin + amphiphilic ion, group C was chitin + quaternary ammonium salt, group D was chitin + amphiphilic ion + quaternary ammonium salt. Results: In the group D material, precipitation of adherent composite ions was observed. The contact angle test showed that the material was hydrophilic. The drug loading rate in groups B, C, and D was 40–50 (ug:mg), the entrapment efficiency was 70%–75% (P>0.05), and the cumulative release percentages were 87.3%, 88.7%, and 90.2% after 72h for group B, C, and D, respectively. The anti-bacterial activity in vitro was in the order D>C>B>A> control (P>0.05). The anti-pollution activity in vitro was in the order D>B>C>A (P<0.05). The cell proliferation inhibition test showed slight proliferation inhibition (P<0.05) only on the seventh day for group D. Seven days after injury, the wound healing rate was in the order D>C> commercial chitin dressing >B>A> control (P<0.05), and the length of the neonatal epithelium also showed the same trend. Additionally, PCNA and CD31 expression indicated that cell proliferation and angiogenesis were enhanced when skin defects were covered with the D group material (P<0.05).Conclusion: chitin-amphiphilic ion/quaternary ammonium salt dressing was successfully prepared. The antibacterial and antipollution effects of the prepared material (group D) were both very good, acting to promote wound healing. Keywords: chitin, amphipathic anion, quaternary ammonium salt, wound healing, anti-infective dressing